(untitled) (Journal Of Educational and Psychological Researches, 2016)
This study aimed to IQ test standardization of Marten Lother Johan which used with childreen of the one stage at primary schools who aged (6) years old in Baghdad (Resafaa and Kharh). The importance of this study are : 1-The importance of childhood and its role to develop the personality. 2-The importance of this age as the child will exposure to different kind of official teaching . 3-The capability for early detection of special category for early intervention in order to provide the necessary care . 4-Using the current test could consider as a predictive tool to screen the intelligent children . In order to achieve the study aim, the researcher had followed the following steps: IQ test of Marten Lother Johan was used with this study which it was translated into Arabic language by Adel Ez-Aldeen Alashwal. The scale includes 12 items which distributed on 12 sub- scale. The test was conducted on number of experts of psychologist and specialize in measurement and evaluation in order to evaluate the validity of items of the scale. According expert’s view, all the items were appropriate and validate. The test was conducted on 400 students (female and male) who were chosen randomly from four primary schools in Baghdad (Resafaa and Kharh) for the academic year 2014-2015. Some statistical analysis were used with the items (difficulty coefficient , discrimination, and validation). Some psychometric properties were conduced: The validity(fase validity and concurrent validity) . Reliability: Cronbach’s alpha was used and the reliability score was( .94). After prepared the items of the test, the test was conducted 800 students of primary schools in order to obtain the standardization of the test. Some recommendation and suggestions were presented in order to develop the study in the future.